Survey on circulation of infectious bronchitis virus strains in Northern Italy - Calogero Terregino; Maria Serena Beato; Giovanni Ortali; Cristian De Battisti; Alessandra Drago (Italian Journal of Animal Science, 2006)
Infectious Bronchitis (IB) still causes significant health problems in the poultry industry with high economic impact. The presence of several serotypes of IB and the emergence of novel ones must be monitored in order to take appropriate action and to adapt the vaccination programmes to the prevalent serotypes. In order to establish which serotypes are circulating in densely populated poultry area (DPPA) of Northern Italy, a surveillance programme has been undertaken during 2004 and 2005. The results of this surveillance programme show the active circulation of 793-B, IT-02, the introduction of a novel strain, known as QXIBV, originally identified in China and the re-emergence of previously circulating serotype as B1648.